Efficient diffusion of superdense lithium via atomic channels for dendrite-free lithium–metal batteries. Issue 1 (29th November 2021) - Zhou, Shiyuan; Chen, Weixin; Shi, Jie; Li, Gen; Pei, Fei; Liu, Sangui; Ye, Weibin; Xiao, Liangping; Wang, Ming-Sheng; Wang, Dan; Qiao, Yu; Huang, Ling; et al.
Abstract : A novel concept of atomic channels within bulk graphite is proposed for the fast diffusion of multi-layered close-packed Li. The feasibility of bulk-diffusion of superdense Li have been verified in the dendrite-free Li metal batteries. Abstract : The non-uniform aggregation of fast-diffused Li on an anode surface would aggravate its tip-effect-induced nucleation/growth, leading to the notorious dendrite growth in Li metal batteries (LMBs). Tuning the Li diffusion on the anode surface has been regarded previously as a mainstream method to induce its uniform deposition, while the diffusion of Li in the anode bulk is usually ignored. Here, conceptually different from the classic surface modification, we propose a molecular tunnelling strategy to construct atomic channels in graphite bulk, which enables the fast diffusion of superdense Li. Density functional theory calculations and ab initio molecular dynamics simulations prove that the bulk diffusion through atomic channels could become a new and dominating path. Its reversible and efficient diffusion has been further visualized by in situ transmission electron microscopy. As a result, when coupled with high-loading LiFePO4 cathodes (20 mg cm −2 ), a high areal capacity and 100% capacity retention are achieved over 370 cycles. Through this work a new strategy is developed based on the bulk-diffusion of superdense Li for dendrite-free LMBs, which can be pervasive in other high-performance energy storage systems.